Integrating Augmented Reality in Islamic Education: A Case Study of Al Ma’arif Singosari High School - Mahliatussikah, Hanik; Ash Shidiqiyah, Firstiyana Romadlon; Tamami, Fazri Nur Insan; Mardatillah, Harrifah; Erwani, Erwani; Wafa, Muhammad Sirril (HEUTAGOGIA: Journal of Islamic Education, 2025)
This study investigates the implementation of Augmented Reality (AR)-based learning media at Al Ma’arif Singosari High School, an Islamic educational institution undergoing digital transformation. Employing a qualitative case study approach, the research explores the lived experiences, perceptions, and challenges encountered by teachers, students, and administrators. Data were collected through classroom observations, semi-structured interviews, focus group discussions, and document analysis, ensuring methodological triangulation. Findings indicate that AR positively influenced teaching practices, fostering creativity and a shift from content delivery to facilitative instruction. Students reported increased engagement and improved comprehension of abstract concepts across subjects such as Islamic Studies, Biology, and Arabic. However, technical challenges—including device compatibility, limited internet connectivity, and distractions from mobile devices—posed significant barriers. These dual outcomes highlight both the pedagogical potential and operational limitations of AR in Islamic education. The study provides practical implications for institutions considering similar initiatives, emphasizing the importance of teacher training, infrastructure readiness, and institutional support. While offering a replicable framework, this single-site study is limited in scope and duration. Future research should explore the long-term impacts of AR integration, its adaptability across diverse Islamic school contexts, and the development of culturally and pedagogically aligned AR content.